K-Anonymity technique for privacy protection: a proof of concept study - Santos, Italo; Coutinho, Emanuel; Moreira, Leonardo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2019)
Privacy is a concept directly related to people's interest in maintaining personal space without the interference of others. In this paper, we focus on study the k-anonymity technique since many generalization algorithms are based on this privacy model. Due to this, we develop a proof of concept that uses the k-anonymity technique for data anonymization to anonymize data raw and generate a new ﬁle with anonymized data. We present the system architecture and detailed an experiment using the adult data set which has sensitive information, where each record corresponds to the personal information for a person. Finally, we summarize our work and discuss future works.